Implementation of a mobile prosthetic and orthotic care program in the VA; a qualitative study of implementation challenges and associated strategies for improvement - Leonard, Chelsea; Young, Jessica; McKown, Lauren; Klassen, Carolyn; Kaufman, George E.; Abrahamson, Daniel (Frontiers in Health Services, 2024)
Introduction –Anticipating and addressing implementation challenges is critical to ensuring success of mobile healthcare programs. Mobile Prosthetic and Orthotic (O&P) Care (MoPOC) is a new U.S. Department of Veterans Affairs (VA) program that aims to improve access to VA-based O&P services through a national network of traveling O&P clinicians who deliver care in rural communities. We conducted an iterative evaluation guided by the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework to identify challenges and associated strategies for successful implementation of this mobile O&P program. Methods – MoPOC is delivered by an O&P clinician anchored at a VA medical center (VAMC). Clinicians travel to remote VA clinics and Veteran’s homes with a custom vehicle which provides storage and a workshop to modify O&P devices. Each clinician is supported by a program support assistant. MoPOC was implemented in three phases. The qualitative evaluation of MoPOC implementation was conducted as part of a larger evaluation of MoPOC program outcomes. We conducted semi-structured interviews and regular check-ins with MoPOC clinicians, site managers, and stakeholders both prior to implementation and throughout the implementation process. Interviews were recorded and transcribed verbatim. Data was analyzed across sites and comparatively by phase using a rapid matrix analysis to identify themes related to adoption and implementation challenges and key strategies developed to address those challenges. Results – We identified four key themes related to successful program implementation, each with associated challenges and improvement strategies: 1) “Finding the right sites for MoPOC” through intentional recruitment and site selection; 2) Identifying the “sweet spot”: Balancing program capacity, sustainability, and MoPOC clinician satisfaction; 3) Shifting from testing to standardizing; and 4) “Being strategic with hiring” to improve program adoption. Discussion – Implementation challenges were related to recruiting and selecting successful sites, ensuring timely program adoption, balancing site level adaptation and program standardization, and scaling programs to enhance efficiency, reach, and satisfaction. An iterative approach guided by the RE-AIM framework resulted in program improvement and more rapid implementation in each successive phase. The challenges described in MoPOC implementation may be common issues in implementing new mobile programs in rural areas.